DAMAGE INTENSITY PESTS AND PATHOGENS IN MANURE DOSAGE TREATMENT ON WHITE GLUTINOUS RICE PLANT - Siswadi; Santosa, Sartono Joko; Setiawan, Arif; Wira, Rahmayani Ayu (Acitya Wisesa: Journal of Multidisciplinary Research, 2022)
This research aims to assess the use of various doses of manure affect the intensity level of pests and pathogens on white glutinous rice plants. This research was conducted from February 2020 to June 2020, in Dibal Village, Ngemplak District, Boyolali Regency with an altitude place 200 meters above sea level with the type of soil Grumosol. This research method uses a single factor randomized complete block design (RCBD) consisting of 10 kinds of experiments and each was repeated 3 times in order to obtain 30 kinds trial. The results showed that bug pest attacks in 70 days after planting with lowest intensity of pest damage, namely 34.02%. While the symptoms of narrow brown spot disease (Cercospora oryzae) were evenly distributed at 40 days after planting with lowest disease intensity, namely 71.43%. The treatment of goat manure at a dose of 1.35 kg / plot (K3) on white glutinous rice (Oryza sativa L glutinosa) can reduce the intensity of damage to stink bug pests. The treatment of chicken manure at a dose of 4.5 kg / plot on glutinous white rice can reduce the intensity of narrow brown spot disease (Cercospora oryzae) on leaves and stems. Then, the treatment of chicken manure at a dose of 4.5 kg / plot on white glutinous rice plants gave the highest yield on grain weight per plot, namely 1820.90 grams (8.67 tons/ha).